Guiding and supporting adolescents living with HIV in sub-Saharan Africa: The development of a curriculum for family and community members. (February 2016) - Winskell, Kate; Miller, Kim S.; Allen, Kristi Ann; Obong'o, Christopher O.
Abstract: Although HIV-related deaths declined globally by 30% between 2005 and 2012, those among adolescents living with HIV (ALHIV) rose by 50%. This discrepancy is primarily due to failure to address the specific needs of ALHIV and resulting poor clinical outcomes related to late diagnosis and poor adherence to antiretroviral therapy. The Families Matter! Program (FMP) is an evidence-based intervention for parents and caregivers of 9–12 year-olds that promotes positive parenting practices and effective parent–child communication about sexuality and sexual risk reduction. It is delivered to groups of participants at the community level through a series of six weekly three-hour sessions. Recognizing family and community members' need for guidance on issues specific to ALHIV, we developed a seventh FMP session to address their needs. Key themes treated in the curriculum for this session include: stigma and mental health, disclosure, ART adherence and self-care, and responsible sexual relationships. In developing the curriculum, we drew on narratives about growing up with HIV contributed by young Africans to a 2013 scriptwriting competition. We describe the data-driven process of developing this curriculum with a view to informing the development of much-needed interventions to serve this vulnerable population. Highlights: Deaths in adolescents living with HIV (ALHIV) doubled from 2005 to 2012. The Families Matter! Program (FMP) is an evidence-based parenting intervention. We developed a new FMP session for family and community members of ALHIV. It is designed to increase guidance and support for ALHIV in sub-Saharan Africa. It draws on narratives contributed by young Africans to a scriptwriting contest.